The Influence of Product Quality, Brand Image, and E-Wom on Repurchase Intention of Samsung Brand Smartphones - I Made Dananjaya; Ni Nyoman Kerti Yasa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The development of information and communication technology has significantly changed consumer behavior, especially in the smartphone industry. Samsung as one of the leading smartphone manufacturers, is ranked first based on data from the 2024 Top Brand Award. Superior product quality, positive brand image, and good e-WOM are estimated to play a significant role in influencing consumer decisions to make repeat purchases. This study aims to determine the effect of product quality, brand image and E-WOM on repurchase intentions. The location of this research is in Tabanan Regency. The data collection technique used is a questionnaire. The population uses the Tabanan Regency community who have used Samsung smartphones, with a sample of 100 respondents. The data analysis techniques used are Descriptive Statistical Analysis, Research Instrument Test, Classical Assumption Test, Multiple Linear Regression, t-Test, F-Test, Determination and Beta Coefficient. Based on the results of the study, it was found that product quality has a positive and significant effect on repurchase intentions, brand image has a positive and significant effect on repurchase intentions, and E-WOM has a positive and significant effect on repurchase intentions. The suggestion that can be given by the researcher is that Samsung is expected to maintain product quality, build a strong brand image, and manage e-WOM well. This is an effective strategy to increase consumer desire and encourage consumers to repurchase.